2020
DOI: 10.1002/eng2.12281
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing and Assessment of an Islanded Photovoltaic‐Battery‐Diesel Generator Microgrid Applicable to a Remote School of Bangladesh

Abstract: Electricity has become a part and parcel of modern life. The world is constantly developing, and the electricity demand is inevitably increasing with it. It is a big challenge for the power generation organizations to cope up with this increasing demand. For a developing country like Bangladesh, this challenge is even bigger. Bangladesh has many remote areas which are deprived of grid connectivity. In this article, system design and performance evaluation are conducted on a solar battery‐based hybrid renewable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…However, thermal load demand and multi-year analysis based on the load growth rate were neglected in their study. Another investigation 16 proposed a similar configuration to Ref. 14 for a remote place in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thermal load demand and multi-year analysis based on the load growth rate were neglected in their study. Another investigation 16 proposed a similar configuration to Ref. 14 for a remote place in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing recent studies in the field, it can be observed that many studies neglected to consider load growth rates in their long-term planning. [10][11][12][13][14][15][16] In these studies, hybrid energy systems are optimized using a one-year electrical (sometimes thermal) load consumption profile and then extrapolate that particular year to other years until the end of the optimization (static planning approach). While this procedure significantly saves simulation time, the results could be unrealistic, especially when the residential sector is taken as a case study.…”
Section: Introductionmentioning
confidence: 99%
“…To introduce these distributed renewable resources into the power system network, microgrids (MG) are an feasible and highly effective solution [1]- [3], particularly since the extension of the conventional power grid often becomes more costly than setting up a MG for a remote offgrid location [4]. The effectiveness of MGs, have been attracted several researchers to the topic [5]- [7], [9], [10], [14] in recently. MGs mainly contain distributed renewable generation sources like wind turbines, fuel cells and photo voltaic (PV) cells that integrate different sources and loads like light emitting diodes (LED) in the system.…”
Section: Introductionmentioning
confidence: 99%
“…MGs mainly contain distributed renewable generation sources like wind turbines, fuel cells and photo voltaic (PV) cells that integrate different sources and loads like light emitting diodes (LED) in the system. Hybrid alternating current (AC)/ direct current (DC) MGs contain both DC and AC buses which can integrate both DC and AC sources and loads in the network [10]. To introduce these sources with conventional power sources, an appropriate energy management system (EMS) is needed [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation